Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
3x - 1y = 5 ⇒ 3x - 1y = 5
1x + 2y = -3 ⇒ 3x + 6y = -9
7y = 14
7 7
y = 2
1x - 2y = -3
1x - 2(2) = -3
1x - 4 = -3
+4 +4
x = 1
(x, y) = (1, 2)
1x + 2y = -3 ⇒ 3x + 6y = -9
7y = 14
7 7
y = 2
1x - 2y = -3
1x - 2(2) = -3
1x - 4 = -3
+4 +4
x = 1
(x, y) = (1, 2)
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.